Republic of Slovenia : Accounting and Auditing - World Bank (Washington, DC, 2013)
This assessment of accounting and auditing practices in Slovenia focuses on the strengths and weaknesses of the accounting and auditing environment that influence the quality of corporate financial reporting, and involves a review of both mandatory requirements, and actual practice. It uses International Financial Reporting Standards (IFRSs), and International Standards on Auditing (ISAs), and the relevant portions of European Union (EU) law (also known as the acquis communautaire) as benchmarks, and draws on international experience and good practices in the field of accounting and audit regulation. Slovenia adopted a gradualist approach to economic reform: the first stage of privatization of socially owned enterprises began in 1992, using different measures, including management and employee buyouts, voucher privatization via investment funds, and direct sales. However, the process resulted in a dispersion of ownership among various state institutions, investment funds (which have remained passive owners), and, most notably, managers and employees. The banking system is relatively well developed by central European standards, and the system is sound and well capitalized, with a low proportion of nonperforming loans. Although the Ljubljana Stock Exchange was established in December 1989, it has failed to challenge the banks as a source of funding for the corporate sector, or a destination for the population's savings. However, a broad range of Slovenian enterprises became listed toward the end of the 1990s. The insurance industry is developing: the state retains an 85 percent stake in the market leader, and, insurance penetration, expressed in terms of premium as a percentage of GDP (5.3 percent including health), is the highest among the transitional Central European countries. As new regulations come into force, priorities are now turning to build the monitoring, supervisory and disciplinary regimes necessary to ensure effective compliance. This assessment demonstrates that the effective enforcement of accounting, auditing and ethical standards is the next challenge that Slovenia has to tackle. This report draws upon recent international experience in developed economies and accession countries, as well as expected amendments to the acquis communautaire, and recommends that Slovenia strengthen the enforcement of accounting and auditing standards.